Emergency Dispatcher Stroke Recognition: Associations with Downstream Care. (4th July 2018) - Oostema, J. Adam; Chassee, Todd; Reeves, Mathew
Abstract: Objective : As the first point of contact for patients activating emergency medical services (EMS), emergency dispatchers have the earliest opportunity to recognize stroke. We sought to quantify dispatcher stroke recognition and its relationships with EMS stroke recognition and response speed.Methods : We assembled a cohort of consecutive EMS-transported patients with a dispatcher suspected stroke or a hospital discharge diagnosis of stroke or transient ischemic attack (TIA). Dispatcher sensitivity and positive predictive value (PPV) for stroke recognition were calculated. Multivariable logistic regression analysis was used to determine predictors of dispatcher recognition and relationships between dispatcher recognition and downstream care.Results : During a 12-month period, 601 patients met inclusion criteria. Dispatchers suspected stroke in 229/324 (sensitivity = 70.7% [65.5 to 75.4%]) confirmed stroke/TIA cases and correctly assigned a suspected stroke label in 229/506 cases (PPV = 45.3% [41.0 to 49.6%]). Dispatchers had higher odds of recognizing ischemic strokes (aOR 3.4 [1.4 to 8.5]) and lower odds of recognizing patients with visual deficits (aOR = 0.4 [0.2 to 0.9]) or vomiting (aOR = 0.3 [0.1 to 0.9]). Dispatcher suspected stroke cases received more on-scene stroke screens (79.0% vs. 54.7%, p < 0.0001) and were more often recognized by EMS as strokes (77.7% vs. 57.9%, p = 0.0005). Dispatcher recognition was independently associated with EMS stroke recognition (aOR = 3.8 [1.9 to 7.7]), but not with transportation times, door-to-CT times, or t-PA delivery.Conclusions : Emergency dispatcher stroke recognition is associated with higher rates of on-scene stroke scale performance and EMS ischemic stroke recognition but not with reduced transport times, door-to-CT times, or t-PA treatment.